2022
DOI: 10.1111/cns.13942
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between chronic hypoxia and seizure susceptibility

Abstract: Chronic hypobaric hypoxia in high-altitude areas can affect the functions of the heart, 1 cerebrovascular system, and respiratory system, impair cognition, accelerate the progression of neurodegenerative diseases, seriously affect the normal physiological function of body systems, and even cause systemic diseases. 2 Qinghai Province is located in northwestern China, with an average elevation of more than 3200 meters. Its natural hypobaric hypoxic environment provides a unique advantage for studying neurologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 93 publications
0
17
0
Order By: Relevance
“…Epilepsy is characterized by unprovoked seizures with manifestations of abnormally synchronized electrical activity due to neuronal hyperexcitability 8 . Previous studies have found that chronic hypoxia can cause higher neuronal excitability, which can lower the epileptic seizure threshold involved in the increase of seizure susceptibility and thus lead to the development of drug‐resistant epilepsy (DRE) 9 . Additionally, ictal hypoxemia is considered as one of the mechanisms underlying sudden unexpected death in epilepsy (SUDEP) 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epilepsy is characterized by unprovoked seizures with manifestations of abnormally synchronized electrical activity due to neuronal hyperexcitability 8 . Previous studies have found that chronic hypoxia can cause higher neuronal excitability, which can lower the epileptic seizure threshold involved in the increase of seizure susceptibility and thus lead to the development of drug‐resistant epilepsy (DRE) 9 . Additionally, ictal hypoxemia is considered as one of the mechanisms underlying sudden unexpected death in epilepsy (SUDEP) 10 .…”
Section: Introductionmentioning
confidence: 99%
“…8 Previous studies have found that chronic hypoxia can cause higher neuronal excitability, which can lower the epileptic seizure threshold involved in the increase of seizure susceptibility and thus lead to the development of drug-resistant epilepsy (DRE). 9 Additionally, ictal hypoxemia is considered as one of the mechanisms underlying sudden unexpected death in epilepsy (SUDEP). 10 However, the association between RLS and epilepsy has never been explored, and the blood oxygen level of patients with epilepsy (PWEs) with and without RLS has never been compared either.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, increasing evidence collectively demonstrates that the hypoxic condition in epileptic neurons is a key feature with multifaceted impacts on neuronal activities and functions. [11] Hypoxia-inducible factor-1a (Hif1a) is a key transcription factor responsible for the regulation of oxygen homeostasis and the activations of multiple drug transporters. [12,13] It is rational to speculate that the hypoxic microenvironment in epileptic brain tissues may activate the Hif1a-Abcb1 signaling axis to express abundant P-gp.…”
Section: Introductionmentioning
confidence: 99%
“…Epilepsy is one of the neurodegenerative diseases that affect people worldwide. This disease can increase the formation of free radicals with recurrent seizures (Xu and Fan 2022). In addition, it has been reported that in epilepsy, prolonged and recurrent seizures may cause lipid peroxidation and mitochondrial dysfunction in peripheral organs such as the liver and kidney, which are sensitive to oxidative stress (Dillioglugil et al 2010).…”
Section: Introductionmentioning
confidence: 99%